Enhanced oxidative depolymerization of lignin in cooperative imidazolium-based ionic liquid binary mixtures. (August 2022) - Gao, Hailian; Wang, Jiebin; Liu, Meixuan; Wang, Shunxin; Li, Wenbo; An, Qingda; Li, Kunlan; Wei, Ligang; Han, Chi; Zhai, Shangru
Graphical abstract: Highlights: CoILs were prepared with [C2 C1 im]OAc/[BZ C1 im]TNf2 of different R IL . Lignin depolymerization in CoILs was conducted under 1.15 MPa O2 at 100 °C. Cooperative effects was found for lignin degradation and product selectivity. Interactions and microstructure of CoILs influenced catalytic properties. CoILs can be recycled and reused in the oxidation at least five times. Abstract: The aerobic oxidation of lignin model 2-phenoxyacetophenone (2-PAP) in cooperative ionic liquid mixtures (CoILs) with 1-ethyl-3-methylimidazolium acetate ([C2 C1 im]OAc) and 1-benzyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([BZ C1 im]NTf2 ) was investigated. Complete degradation of 2-PAP was achieved with [C2 C1 im]OAc/[BZ C1 im]NTf2 molar ratio ( R IL ) of 1/1 and 1/2 at 100 °C for 2 h. The conversion and product yields from CoILs were higher than those in pure ILs, indicating the cooperative effects of [C2 C1 im]OAc/[BZ C1 im]NTf2 on cleaving aryl–ether bonds. [C2 C1 im]OAc promoted the catalytic cleavage of aryl–ether bonds and solvation, and [BZ C1 im]NTf2 induced the formation of alkyl radicals and enhanced the product selectivity. Accordingly, the highest conversion of alkali lignin (79.8%) was obtained with R IL of 5/1 at 100 °C for 2 h, and phenol monomers (306 mg/g) were selectively produced. The CoILs exhibited good catalytic capacities for oxidative depolymerization of lignin, which strongly depends on the changes in intermolecular interactions and structural organization with varying R IL .